Begonia intermedia, an illegitimate name and taxonomic synonym of B. wuzhishanensis - Tian, Daike (Phytotaxa, 2014)
It came to our attention that Begonia ×intermedia Veitch ex van Houtte (1873: 39) was published in Flore des Serres and therefore, B. intermedia D.K. Tian et al. (2014: 116) is a later homonym and not legitimate according to the International code of nomenclature for algae, fungi and plants (McNeill et al. 2012: Art. 53). Furthermore, the article by Tian et al. was published on 24 Apr 2014 in Phytotaxa while B. wuzhishanensis C.I. Peng et al. (2014: 3) was published on 5 Feb 2014 in Botanical Studies for the same species based on type material collected from different locations on Hainan Island of China. In total, extant wild populations of this species have been found in at least the three places belonging to one city (Wuzhishan) and two counties (Qiongzhong and Lingshui), respectively (Fig 1).